Field notes contributed by Eugene Armstrong and Eloise Armstrong, fall 1987 - Armstrong, Eloiseet al; Armstrong, Eugeneet al (1987)
Fall report of birds contributed by Eugene Armstrong and Eloise Armstrong. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1987. Epson - sheet feed